How to prove that i don't need to find a discriminant to solve the quadratic y^2+6y+9=0?

Expert Answers

An illustration of the letter 'A' in a speech bubbles

The solutions of the quadratic equation y^2 + 6y + 9 = 0 can easily be found without finding the discriminant.

y^2 + 6y + 9 = 0

=> y^2 + 3y + 3y + 9 = 0

=> y( y + 3) + 3(y + 3) = 0

=> (y + 3)^2 = 0

=> y = -3

Or you can use the formula (a + b)^2 = a^2 + b^2 + 2ab.

The solution of the quadratic equation obtained without finding the discriminant is -3

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial